![image](https://tex.z-dn.net/?f=5%2A%28%5Cfrac%7B5%7D%7B6%7D%29%5E%7Bx-1%7D-9%2A%5Cfrac%7B6%7D%7B5%7D%5Ex%2B3%3D0%5C%5C6%2A%5Cfrac%7B5%7D%7B6%7D%5Ex-9%2A%5Cfrac%7B6%7D%7B5%7D%5Ex%2B3%3D0%3B%5Cfrac%7B5%7D%7B6%7D%5Ex%3Da%3Ba%3E0%5C%5C6a-%5Cfrac%7B9%7D%7Ba%7D%2B3%3D0%7C%2A%5Cfrac%7Ba%7D%7B3%7D%5C%5C2a%5E2-3%2Ba%3D0%5C%5C2a%5E2%2Ba-3%3D0%5C%5Ca_%7B1%2C2%7D%3D%5Cfrac%7B-1%5E%2B_-5%7D%7B4%7D%5C%5Ca_1%3D-%5Cfrac%7B3%7D%7B2%7D%3B+%5C+a_2%3D1%5C%5C.%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5Cfrac%7B5%7D%7B6%7D%5Ex%3D1%5C%5C.%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+%5C+x%3D0)
0\\6a-\frac{9}{a}+3=0|*\frac{a}{3}\\2a^2-3+a=0\\2a^2+a-3=0\\a_{1,2}=\frac{-1^+_-5}{4}\\a_1=-\frac{3}{2}; \ a_2=1\\.\ \ \ \ \ \ \ \ \ \ \ \ \frac{5}{6}^x=1\\.\ \ \ \ \ \ \ \ \ \ \ \ \ x=0" alt="5*(\frac{5}{6})^{x-1}-9*\frac{6}{5}^x+3=0\\6*\frac{5}{6}^x-9*\frac{6}{5}^x+3=0;\frac{5}{6}^x=a;a>0\\6a-\frac{9}{a}+3=0|*\frac{a}{3}\\2a^2-3+a=0\\2a^2+a-3=0\\a_{1,2}=\frac{-1^+_-5}{4}\\a_1=-\frac{3}{2}; \ a_2=1\\.\ \ \ \ \ \ \ \ \ \ \ \ \frac{5}{6}^x=1\\.\ \ \ \ \ \ \ \ \ \ \ \ \ x=0" align="absmiddle" class="latex-formula">